1999
DOI: 10.1046/j.1365-313x.1999.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

A rapid method for detection of plant gene transcripts from single epidermal, mesophyll and companion cells of intact leaves

Abstract: SummaryA protocol for the detection of gene transcripts from single plant cells in living, undamaged plant tissue is described. Samples of leaf epidermal, mesophyll and companion cells were extracted by using glass microcapillaries and directly subjected to RT±PCR without any puri®cation steps nor time consuming construction of cDNA libraries. The procedure is not restricted to surface cells or outer cell layers. Even cells from the central region of leaves could be harvested. For identi®cation, companion cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 21 publications
4
66
1
Order By: Relevance
“…This work extends that of Karrer et al (1995); Brandt et al (1999) and Koroleva et al (2001) in establishing SC-RT-PCR as a technique applicable to plant cells. Here we have demonstrated that the technique can be applied successfully to identify patterns of expression of the different but related members of a single family of homologous genes, each of which is present at only moderate abundance (Karrer et al 1995).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…This work extends that of Karrer et al (1995); Brandt et al (1999) and Koroleva et al (2001) in establishing SC-RT-PCR as a technique applicable to plant cells. Here we have demonstrated that the technique can be applied successfully to identify patterns of expression of the different but related members of a single family of homologous genes, each of which is present at only moderate abundance (Karrer et al 1995).…”
Section: Discussionmentioning
confidence: 56%
“…Naturally occurring transcripts (in this case RBCS) can be used as both positive and negative controls. This can be further extended using tissue-specific transgenes (Brandt et al 1999). Here we have used a simple PCR detection system to determine whether the level of particular individual transcripts is greater than an as yet not fully quantified detection limit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Moreover, the possibility to extract RNA from specific and small organs would allow the monitoring of gene expression at a higher tissue resolution (Brandt et al, 1999). Consequently, this micro-scale method offers the possibility to study specific gene expression during developmental processes (i.e.…”
Section: Resultsmentioning
confidence: 99%